2015
DOI: 10.1142/s2010135x15500277
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure, dielectric, ferroelectric and energy storage properties of La-doped BaTiO3 semiconducting ceramics

Abstract: Polycrystalline La-doped BaTiO 3 (Ba ð1ÀxÞ La x TiO 3 ) [x ¼ 0; 0:0005; 0:001; 0:003] ceramics (denoted as BTO,BLT1,BLT2,BLT3) were synthesized by conventional solid-state reaction method and characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and Raman spectroscopy. XRD and Raman spectra revealed single-phase tetragonal perovskite crystalline structure. Well-saturated polarization-electric field (P-E) hysteresis loops were observed with the measurement frequency of 50 Hz at room temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 34 publications
2
33
0
1
Order By: Relevance
“…Figure A displays the Raman spectra of the BTCS‐ x ceramics, while the enlarged spectra at the wave number of 100‐400 cm −1 and the variation in the vibration modes with x are shown in Figure B,C, respectively. As well‐known, the pure BT possesses a perovskite structure at room temperature, and each unit cell contains five atoms . Therefore, for the pure BT, there are 12 kinds of optical vibration mode (3F 1u + 1F 2u ) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure A displays the Raman spectra of the BTCS‐ x ceramics, while the enlarged spectra at the wave number of 100‐400 cm −1 and the variation in the vibration modes with x are shown in Figure B,C, respectively. As well‐known, the pure BT possesses a perovskite structure at room temperature, and each unit cell contains five atoms . Therefore, for the pure BT, there are 12 kinds of optical vibration mode (3F 1u + 1F 2u ) .…”
Section: Resultsmentioning
confidence: 99%
“…As well‐known, the pure BT possesses a perovskite structure at room temperature, and each unit cell contains five atoms . Therefore, for the pure BT, there are 12 kinds of optical vibration mode (3F 1u + 1F 2u ) . When the phase structure of the materials transforms to T phase, the F 1u splits into the A 1 and E modes, and F 2u splits into the B 1 and E modes .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectrum was measured in the range of wavenumber 4000–400 cm −1 . The formation of perovskite structure of the ceramic nanoparticles was supported by FTIR analysis . No peaks were observed for Lanthanum in the graph.…”
Section: Resultsmentioning
confidence: 91%
“…Here they reported that the Curie temperature increased with La content in the ceramic. The obtained Curie temperature was in the range of 415–420 K . The electrical properties of the La doped barium titanate ceramics were studied by F. D. Morrison et al .…”
Section: Introductionmentioning
confidence: 99%